PELATIHAN 3D PRINTING UNTUK JURUSAN KENDARAAN RINGAN SMK DHUAFA PADANG - Sumiati, Ruzita; Leni, Desmarita; Fajri Arsyah, Ahmad Hasnul; Nusyirwan, Nusyirwan; Nofriadi, Nofriadi; Adriansyah, Adriansyah; Nasirwan, Nasirwan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
3D Printing training has been implemented as part of efforts to develop technical competence in vocational education, especially for students of the Light Vehicle Department at SMK Dhuafa Padang. This study aims to assess the effectiveness of 3D Printing training in improving students' skills in the application of additive manufacturing technology in the automotive sector. The training methods applied include the delivery of theoretical materials, technical demonstrations, and exercises. Evaluation of the effectiveness of the training was conducted through comparative analysis of pre-test and post-test results, which aims to measure the improvement of participants' competence before and after attending the training. The results of data analysis showed a significant increase in students' mastery of concepts and technical skills, especially in the use of 3D printing technology for component manufacturing. This training is expected to be a relevant and adaptive learning model, in order to prepare SMK graduates to face the dynamics of the automotive industry which is increasingly based on technology and innovation